From a Marxist Aesthetic to a Critical-Aesthetic Citizen Subject - Wikström, Josefine (The Nordic Journal of Aesthetics, 2025)
This article proposes a shift away from the pursuit of a unified Marxist aesthetics towards an understanding of aesthetics as a constitutive dimension of modern subjectivity, specifically through Étienne Balibar’s concept of the “citizen subject.” Rather than deriving Marxist aesthetics from positive criteria, the argument proceeds in two movements. First, it reconstructs Kant’s transcendental aesthetic subject, in which aesthetics functions not as a theory of taste but as the a priori conditions of sensibility that ground experience and cognition. Second, it examines Balibar’s historicization of this subject, showing how the modern subject emerges as a contradictory “citizen subject,” simultaneously free and subjected, shaped by the political rupture of the French Revolution and the universalist paradoxes it inaugurated. Through close engagement with Balibar’s critique of several misreadings of Descartes (from Heidegger onwards) and with his account of the emergence of modern citizenship, the article argues that the transcendental aesthetic subject embodies what Balibar calls an “intense universality” marked by continual political struggle and indeterminacy. In conclusion, the article reflects on the implications of this figure for Marxist aesthetics today. Ultimately the article suggests that any Marxist aesthetics must take as its point of departure a historically constituted, dialectically split, critical–aesthetic citizen subject capable of a reflexive and sensuous critique of contemporary social forms, such as art, culture, and education.